2013
DOI: 10.1055/s-0040-1705678
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead concentration in breast milk and blood of lactanting women in an interior city of Brasil

Abstract: Background: breast milk offers numerous advantages biological and emotional. However, in some situations, can transfer harmful elements for the health of infants. Objective: to determine lead levels in the blood and milk of mothers whose children frequent a primary mother-child health care. Methods: a cross-sectional, observational and descriptive study of 70 healthy women who were breast-feeding babies younger than six months during 01/04/2011 to 30/09/2011. Lead determination was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Andrade et al. (2013) identified the concentration of Pb in blood of nursing mothers in an inland city of Brazil using the Mass Spectrometer with the associated inductive plasma, where found that the average Pb was 0.01801 ppm [ 40 ]. li et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrade et al. (2013) identified the concentration of Pb in blood of nursing mothers in an inland city of Brazil using the Mass Spectrometer with the associated inductive plasma, where found that the average Pb was 0.01801 ppm [ 40 ]. li et al.…”
Section: Resultsmentioning
confidence: 99%
“…The tools are washed using tap water and deionized water, after that, it dried in the oven at 90 °C for 2 h. All samples were prepared at room temperature of 20 °C. Milk samples (2 ml) are diluted with 1 ml of H 2 O 2 + 2 ml of HNO 3 [ 40 ] and 10 ml of deionized water. Then, the mixture was completed in 25 ml of deionized water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reduces the risk of breast cancer later in life. Environmental pollutants such as metals had been on the increase with increase population due to industrialization and urbanization [8] . Pregnant women and nursing mothers are exposed to such metal pollutants on daily basis.…”
Section: Introductionmentioning
confidence: 99%